Darwinian paradigm, cultural evolution and human purposes: On F.A. Hayek's evolutionary view of the market - Viktor J. Vanberg (Max Planck Institute of Economics, 2011)
The claim that the Darwinian paradigm of blind-variation-and-selective-retention can be generalized from the biological to the socio-cultural realm has often been questioned because of the critical role played by human purposeful design in the process of cultural evolution. In light of the issue of how human purposes and evolutionary forces interact in socio-economic processes the paper examines F.A. Hayek's arguments on the extended order of the market, in particular the tension that exists between his rational liberal and his agnostic evolutionary perspective.
Keywords: 330; Bioökonomik; Evolutionsökonomik; Wirtschaftskultur; Marktmechanismus; Wirtschaftsliberalismus; Theorie